Brexit means Brexit: a constructionist analysis - Mompean, Jose A.; Valenzuela Manzanares, Javier (Complutense Journal of English Studies, 2019)
This paper presents a corpus-assisted discourse analysis of the Brexit means Brexit tautology from a constructionist perspective. A multimodal corpus of instances of the construction was compiled and analyzed, paying attention to the components of the construction such as its phonetic-phonological and gestural features as well as the idealized cognitive models underlying the use of the tautology in discourse. This study also addresses how different semantic-pragmatic uses have an impact on the linguistic form (e.g. prosody, gesture) and emphasizes the fluid interaction between linguistic meaning/form and the social and cultural context in which language is used. It is argued that a full understanding of any construction requires a multimodal, discourse-based analysis.